Soluble Fc Receptor for IgM in Sera From Subsets of Patients With Chronic Lymphocytic Leukemia as Determined by a New Mouse Monoclonal Antibody - Mahmoudi Aliabadi, Pedram; Teuber, Ruth; Jani, Peter K.; Wilson, Landon; Enghard, Philipp; Barnes, Stephen; Chiorazzi, Nicholas; Radbruch, Andreas; Melchers, Fritz; Kubagawa, Hiromi (Frontiers in Immunology, 2022)
The FcR for IgM (FcµR) is the newest member of the FcR family, selectively expressed by lymphocytes, and distinct from FcRs for switched Ig isotypes that are expressed by various immune cell types and non-hematopoietic cells. From studies of Fcmr-ablated mice, FcµR was shown to have a regulatory function in B-cell tolerance, as evidenced by high serum titers of autoantibodies of the IgM and IgG isotypes in mutant mice. In our previous studies, both cell-surface and serum FcµR levels were elevated in patients with chronic lymphocytic leukemia (CLL), where antigen-independent self-ligation of BCR is a hallmark of the neoplastic B cells. This was assessed by sandwich ELISA using two different ectodomain-specific mAbs. To determine whether the serum FcµR is derived from cleavage of its cell-surface receptor (shedding) or its alternative splicing to skip the transmembrane exon resulting in a 70-aa unique hydrophilic C-terminus (soluble), we developed a new mouse IgG1κ mAb specific for human soluble FcμR (solFcμR) by taking advantages of the unique nature of transductant stably producing His-tagged solFcµR and of an in vivo differential immunization. His-tagged solFcμR attached to exosomes and plasma membranes, allowing immunization and initial hybridoma screening without purification of solFcμR. Differential immunization with tolerogen (membrane FcμR) and immunogen (solFcμR) also facilitated to generate solFcμR-specific hybridomas. The resultant solFcμR-specific mAb reacted with serum FcµR in subsets of CLL patients. This mAb, along with another ectodomain-specific mAb, will be used for verifying the hypothesis that the production of solFcµR is the consequence of chronic stimulation of BCR.